Construction of Cu3P-ZnSnO3-g-C3N4 p-n-n heterojunction with multiple built-in electric fields for effectively boosting visible-light photocatalytic degradation of broad-spectrum antibiotics - Guo, Feng; Huang, Xiliu; Chen, Zhihao; Cao, Longwen; Cheng, Xiaofang; Chen, Lizhuang; Shi, Weilong (Separation and purification technology, 2021)
•Cu3P-ZnSnO3-g-C3N4 p-n-n heterojunction was synthesized by a solvothermal route.•Cu3P-ZnSnO3-g-C3N4 shows outstanding visible-light photocatalytic activity.•Multiple built-in electric fields in heterojunction facilitate charge transfer. The design of advanced semiconductor photocatalysts is an effective approach to promote environmental remediation. The p-n-n heterojunction photocatalyst has a strong built-in electric field in the photocatalytic reaction, which provides an effective space for the separation of photo-generated carriers, thereby achieving high-efficient photocatalytic activity. Herein, a facile solvothermal method was developed to manufacture a unique Cu3P-ZSO-CN p-n-n heterojunction photocatalyst for the photodegradation of broad-spectrum antibiotics under visible light irradiation. Benefiting from the novel p-n-n heterojunction structure, the obtained 5% Cu3P-ZSO-CN photocatalyst exhibits the highest degradation efficiency, and the degradation rates for tetracycline (TC), oxytetracycline (OTC), chlortetracycline (CTC) and ciprofloxacin (CIP) are assigned to 98.45%, 54.71%, 63.52% and 87.57%, respectively. Furthermore, based on the detection of intermediate products via liquid chromatography mass spectrometry (LC-MS), the possible photodegradation pathway of TC was analyzed. Finally, the possible Cu3P-ZSO-CN p-n-n heterojunction photocatalytic reaction mechanism was revealed in detail by the examination of optical properties and capturing experiments of active species. This work provides a new perspective for the application of p-n-n heterojunction photocatalysts in environmental remediation.